2020
DOI: 10.21037/atm.2020.02.129
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol ingestion induces pancreatic islet dysfunction and apoptosis via mediation of FGF21 resistance

Abstract: Background: Disruption of β-cell insulin secretion and viability caused by excessive ethanol consumption increases type 2 diabetes mellitus (T2DM) pathogenesis risk. Fibroblast growth factor 21 (FGF21) plays a significant role in regulating lipid and glucose homeostasis. Recently, FGF21, best known for its role in lipid and glucose homeostasis regulation, and its obligate co-receptor β-klotho have been shown to inhibit ethanol ingestion and metabolism. It remains unclear whether heavy ethanol intake modulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…However, no significant changes were observed in LVIDs, EF and FS. In addition, our results confirm that long-term ethanol consumption induces insulin resistance and thus diabetes pathogenesis risk, which was consistent with Yang, Wu & Leung (2020) . In view of the heart dysfunction and myocardial insulin resistance caused by ethanol, reducing alcohol consumption might be metabolically favorable for human future glucose metabolism.…”
Section: Discussionsupporting
confidence: 89%
“…However, no significant changes were observed in LVIDs, EF and FS. In addition, our results confirm that long-term ethanol consumption induces insulin resistance and thus diabetes pathogenesis risk, which was consistent with Yang, Wu & Leung (2020) . In view of the heart dysfunction and myocardial insulin resistance caused by ethanol, reducing alcohol consumption might be metabolically favorable for human future glucose metabolism.…”
Section: Discussionsupporting
confidence: 89%
“…It is reported that excessive alcohol is a significant risk factor in β‐cell apoptosis 1‐3 . To examine whether LNT could prevent ethanol‐induced β‐cell apoptosis, MIN6 cells were pretreated with LNT for 2 hours and then exposed to ethanol for an additional 72 hours.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic alcohol consumption is well established as a major risk factor to trigger the development of type 2 diabetes mellitus (T2DM), which is evidenced by impaired glucose metabolism and insulin resistance 1‐3 . Due to the key role of pancreatic β‐cell failure in the pathogenesis of T2DM, increasingly more attention has been paid to the understanding of β‐cell damage induced by excessive heavy ethanol in recent years 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that alcohol intake of more than 3–5 drinks/day can dramatically increase the energy intake from alcohol. 7 , 8 More importantly, chronic heavy drinking has been proven to induce pancreatic β-cell dysfunction in human and animal models, 11 , 12 with decreased insulin-secretory ability and disrupted glucose homeostasis. Both increased energy intake and pancreatic β-cell dysfunction contribute to the pathogenesis of obesity in heavy drinkers.…”
Section: Alcohol Consumption and Overweight/obesitymentioning
confidence: 99%